Short-distance seed and pollen dispersal in both hunted and intact forests in the lower canopy African rainforest tree, Coula edulis Baill. (Coulaceae) - Kamdem, G.; Sonke, B.; Sergeant, S.; Deblauwe, V.; Hardy, O.J. (2025)
Mammal-dispersed tropical trees can face regeneration problems due to increasing hunting pressure. We studied the case of Coula edulis Baill. (Coulaceae), an African rainforest tree that produces the ‘African walnut’, an essential food and income resource for rural communities. We compared gene flow and regeneration dynamics in three populations with contrasting levels of human disturbance and mammal abundance. Using 21 nuclear microsatellite markers, we estimated the outcrossing rate and contemporary seed and pollen dispersal distances, and we analyzed the fine-scale spatial genetic structure (FSGS) to infer historical gene dispersal distances.